Application of the Time Token Arrends Method to Make Students Active and Skilled in Speaking in Indonesian Learning Class V Madrasah Ibtidaiyah Baitul Hikmah Panaan Palengaan Pamekasan - Al Ayyubi, Sholahuddin (Journal of Islamic Elementary Education, 2023)
This study examines the application of the Arends time token method in learning related to speaking skills. This is the main problem in this research. Furthermore, through this research it can be described regarding active and skilled students in speaking class V students at MI Baitul Hikmah Panaan ‎Palengaan Pamekasan. Thus, the purpose of this study is to make students more active and skilled at speaking when teaching and learning activities take place. The approach and type of research in this study is a qualitative approach, namely a research procedure that produces descriptive data in the form of speech or writing and observable behavior from the subject itself. This type of research is case study, namely this type of case study approach is a type of approach used to investigate and understand an incident or problem that has occurred by collecting various kinds of information which is then processed to obtain a solution so that the problem uncovered can be resolved. . The research results obtained in this study are that the application of the time token arrends method is very effective, simple, because in the application of the time token arrends method it does not use a lot of tools and media so it does not require a lot of money, as well as in research results In this case,  students and teachers feel helped because the teaching and learning activities in the class are all active students (live learning) and students feel increasingly challenged and more confident to dare to speak skillfully and provide stimulus for them to be more active in learning.